Room-temperature serial crystallography using a kinetically optimized microfluidic device for protein crystallization and on-chip X-ray diffraction. (2014) - Heymann, M.; Opthalage, A.; Wierman, J. L.; Akella, S.; Szebenyi, D. M. E.; Gruner, S. M.; Fraden, S.
No abstract available